ANALISA PENGARUH KEPEMIMPINAN TERHADAP KUALITAS KERJA KARYAWAN PT. BANK MAYORA - Sendianto Sendianto; Bambang Ermansyah Saragih; Hendri Hendri (Sekolah Tinggi Manajemen IMMI, 2022)
Companies in carrying out their business activities need to pay attention to internal and external aspects. Leadership is one of the internal aspects that affect the behavior of a company in carrying out business activities. Performance or performance is the result of work that can be achieved by a person or group of people in the organization, in accordance with their respective authorities and responsibilities. Quality of work is a result that can be measured by the effectiveness and efficiency of a job done by human resources or other resources in achieving the goals or objectives of the company well and efficiently. This shows that the leadership process is the main indicator in improving the quality of work of the employees themselves. The problem is that there is still a lack of harmony between superiors and subordinates and the lack of leadership styles in several companies, causing the performance or quality of work of employees to be disrupted and have a direct impact on the company. Based on this background, the research title